LEARNING DESIGN OF SEQUENCE AND SERIES OF ARITHMETIC USING THE CONTEXT OF SONGKET PALEMBANG - Hardiyanti Indriani; Ratu Ilma Indra Putri; Darmawijoyo Darmawijoyo (Sriwijaya University Learning and Education International Conference, 2018)
The aim of this research is to know the part of learning trajectory supporting the student understanding on learning arithmetic sequence and series using tradisional handycraft songket Palembang with PMRI approach and describe learning students activity proccess of class X in learning mathematics so that can develop informal activity become formal when learning arithmetic sequence and series. The method used in this study is the Design Research that consists of three stages: preliminary, design of experiment (pilot experiments and teaching experiment) and restrospective analysis. The subjects consisted of 29 students of class X. This study resulted in Learning Trajectory (LT), which contains a series of learning process that helps students find the concept of arithmetic sequence and series. At the informal level, students use the context of songket Palembang to find rules of arithmetic sequence and series. In preformal level, students begin composing and drawing motif images of songket as of arithmetic sequences, using pieces of motifs songket as a model of what they consider to be a songket which led to a model for the arithmetic sequences in finding the n and number of first n terms of arithmetic series. While on a formal level the students is able to resolve the problem by using contextual knowledge and their experience at the previous level